UPAYA PASANGAN SUAMI-ISTRI TUNADAKSA DALAM MEMBENTUK KELUARGA SAKINAH: : Studi Kasus di Desa Putat Lor Gondanglegi Malang - Rudy Catur Rohman Kusmayadi (LP3M IAI Al-Qolam, 2021)
The sakinah family is formed by two words, namely family and sakinah. The meaning of the family is the smallest community consisting of at least a husband and wife as the main source along with children. The word sakinah itself can be found in the Qur'an, so that you tend and feel at ease with it, so that it can be concluded that the basic conclusion is that the Qur'an teaches mankind to build a family that is sakinah, which is peaceful, to be more peaceful in life. . The concept of a sakinah family in general is also explained in the Qur'an Surah Ar-Rum verse 21. A sense of understanding, mutual acceptance of the condition of the partner, peaceful and strong in dealing with every problem that exists, is what is understood by a quadriplegic couple. Even though there are differences in understanding between them, basically what is most needed in achieving a sakinah family according to them is a sense of mutual understanding between family members.